Cycle-related Diarrhea and Dysmenorrhea are Independent Predictors of Peritoneal Endometriosis, Cycle-related Dyschezia is an Independent Predictor of Rectal Involvement - Nicolaus, Kristin; Reckenbeil, Laura; Bräuer, Dominik; Sczesny, Robert; Diebolder, Herbert; Runnebaum, Ingo B. (Geburtshilfe und Frauenheilkunde, 2020)
Introduction The clinical presentation of endometriosis is extremely varied. Because endometriosis symptoms may overlap with symptoms caused by gastroenterological disorders, this can lead to misdiagnosis and a considerable delay in arriving at the correct diagnosis. The aim was to evaluate the type and duration of endometriosis-related symptoms and to identify predictors for patterns of involvement depending on symptoms.Material and Method The data of 266 consecutive patients who were operated on in the Endometriosis Center between 1/2016 and 12/2017 after receiving a histologically verified diagnosis of endometriosis were recorded. In addition to recording the clinical parameters, a questionnaire was distributed to the patients, who were asked about their medical history. Infertile patients were grouped together as Group 1 and compared to non-infertile patients (Group 2).Results The response rate for returned questionnaires was 79.47% (182/229). 41.8% of patients reported that they were infertile and 91.8% reported pelvic pain. In more than ⅓ of cases in both groups, more than 10 years passed between the initial symptoms and the final diagnosis (39.4 vs. 37.5%). On average, patients consulted 2.72 (± 1.58) resp. 3.08 (± 1.72) doctors before they presented to a hospital or were referred for laparoscopic diagnostic workup (p = 0.162). Cycle-related diarrhea (odds ratio 2.707; 95% CI: 1.063 – 6.895, p = 0.037) and dysmenorrhea (odds ratio 2.278; 95% CI: 1.193 – 4.348, p = 0.013) were associated with involvement of the pelvic peritoneum, cycle-related dyschezia was associated with rectal involvement by a factor of 4.6 in binary regression analysis (odds ratio 4.659; 95% CI: 1.132 – 19.186; p = 0.033).Conclusion Cycle-related diarrhea and dysmenorrhea increase the risk probability of peritoneal endometriosis. Dyschezia increases the risk probability of rectal endometriosis.Einleitung Das klinische Erscheinungsbild der Endometriose ist vielfältig. Durch die mit gastroenterologischen Erkrankungen überlappenden Symptome kann es zu Fehldiagnosen und erheblicher Verzögerung der Diagnosestellung kommen. Ziel war es, die Art und Dauer der endometrioseassoziierten Symptome zu evaluieren sowie Prädiktoren für Befallsmuster in Abhängigkeit von den Beschwerden zu identifizieren.Material und Methode Es erfolgte eine Erfassung von 266 konsekutiven Patientinnen, die im Zeitraum von 1/2016 bis 12/2017 aufgrund einer histologisch gesicherten Endometriose am Endometriosezentrum operiert wurden. Zusätzlich zur Erfassung klinischer Parameter wurden die Patientinnen über einen Fragebogen zu ihrer Krankengeschichte befragt. Patientinnen mit Sterilität wurden als Gruppe 1 den Patientinnen ohne Sterilität (Gruppe 2) gegenübergestellt.Ergebnisse Die Rücksenderate der Fragebögen betrug 79,47% (182/229). 41,8% berichteten über eine Sterilität und 91,8% über Unterbauchschmerzen. Von Erstsymptom bis Diagnosestellung vergingen in beiden Gruppen in mehr als ⅓ der Fälle über 10 Jahre (39,4 vs. 37,5%). Bis zur Vorstellung in einer Klinik bzw. bis zur Indikation der laparoskopischen Diagnostik wurden im Mittel 2,72 (± 1,58) bzw. 3,08 (± 1,72) Ärzte aufgesucht (p = 0,162). Zyklusabhängige Diarrhö (Odds Ratio 2,707, 95%-KI 1,063 – 6,895, p = 0,037) und Dysmenorrhö (Odds Ratio 2,278, 95%-KI 1,193 – 4,348, p = 0,013) waren mit einem Befall des Beckenperitoneums assoziiert, die zyklusabhängige Dyschezie war mit dem Befall des Rektums um den Faktor 4,6 in der binären Regressionsanalyse assoziiert (Odds Ratio 4,659; 95%-KI 1,132 – 19,186; p = 0,033).Schlussfolgerung Zyklusabhängige Diarrhö und Dysmenorrhö erhöhten das Risiko für das Vorhandensein einer peritonealen Endometriose. Dyschezie erhöhte das Risiko einer Rektumendometriose.
Keywords: endometriosis; dysmenorrhea; dyschezia